(3ehfGehQs "(3dc MHj(B"s - (3GdTGWQ, fgis; (3ShGM, SGde YHO GdeYRs; (3UdGM, eQhIs ((3GdefhajI, eUQs (3MhGOjJ ddfTQs, 2023)
(3YfOeG JDdec PcQjGJ GdeGVj hjfhA bdHc HgRGFe GdOfjG hGfcSGQGJ GdMjGI, YfOeG jYPHc MGVQ eQjQ JJYGjT ajg eY NjHGJ bdHc hNPdGf ef JMH, GgQH Edi GdeSJbHd dYdg jMed fLGJc hJQO GdUaYI ddMjGIs
1 3 12 13
Keywords: (3GdCOH GdYQHjs; (3GdbUU GdYGWajIs; (3GdbUU GdYQHjIs -- (3eUQs